Unmet supportive care needs of people with advanced cancer and their caregivers: A systematic scoping review. (August 2022) - Hart, Nicolas H.; Crawford-Williams, Fiona; Crichton, Megan; Yee, Jasmine; Smith, Thomas J.; Koczwara, Bogda; Fitch, Margaret I.; Crawford, Gregory B.; Mukhopadhyay, Sandip; Mahony, Jane; Cheah, Chan; Townsend, James; et al.
Abstract: Examining and addressing unmet care needs is integral to improving the provision and quality of cancer services. This review explored the prevalence of unmet supportive care needs, and factors associated with unmet need, in adults with advanced cancers (solid and hematological malignancies) and their caregivers. Electronic databases (PubMed, CINAHL, EMBASE) were searched, producing 85 papers representing 81 included studies. People with advanced cancer reported the highest unmet needs in financial, health system and information, psychological, and physical and daily living domains, whereas caregivers reported the highest unmet needs in psychological, and patient care and support domains. Distress, depression, and anxiety were associated with higher unmet needs across all unmet need domains for people with advanced cancer and their caregivers. Substantial heterogeneity in study populations and methods was observed. Findings from this review can inform targeted strategies and interventions to address these unmet needs in people with advanced cancer. Graphical Abstract: ga1 Highlights: Distress, depression, and anxiety are associated with unmet needs across domains. Patients and carers share high unmet psychological needs as most prevalent. Patients report unmet informational, financial, physical needs as most prevalent. Carers report high unmet care and support needs of patients as most prevalent. There was substantial heterogeneity, warranting further research with validated tools.